1996
DOI: 10.2337/diab.45.5.695
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Leptin and Insulin Relationships in Obese and Nonobese Humans

Abstract: Hyperinsulinemia. is associated with an overexpression of mRNA for the ob protein leptin in rodent models of genetic obesity, and insulin has been reported to directly stimulate leptin mRNA in rat adipocytes. Human obesity is also associated with increased leptin mRNA as well as plasma levels, but there have been no reports of the effect of insulin on leptin secretion. We, therefore, tested the hypothesis that insulin stimulates leptin secretion in humans. Using a newly developed leptin assay, immunoreactive l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
138
6
8

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 323 publications
(177 citation statements)
references
References 15 publications
25
138
6
8
Order By: Relevance
“…Together, these findings suggested that relatively large increases in serum insulin levels (Ͼ 200 pM) were needed for relatively long periods of time (Ͼ 24 h) before serum leptin levels rose significantly. These results are in accord with reports by several groups, who, with one exception, all failed to find effects of acute (up to 5 h) hyperinsulinemia on leptin levels (10)(11)(12)(13)(14)(15)(16). The sole exception, a study by Utriainen et al (16), reported an ‫ف‬ 50% increase in serum leptin after 4 h of unphysiologic high insulin levels ‫ف(‬ 2,800 pM).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Together, these findings suggested that relatively large increases in serum insulin levels (Ͼ 200 pM) were needed for relatively long periods of time (Ͼ 24 h) before serum leptin levels rose significantly. These results are in accord with reports by several groups, who, with one exception, all failed to find effects of acute (up to 5 h) hyperinsulinemia on leptin levels (10)(11)(12)(13)(14)(15)(16). The sole exception, a study by Utriainen et al (16), reported an ‫ف‬ 50% increase in serum leptin after 4 h of unphysiologic high insulin levels ‫ف(‬ 2,800 pM).…”
Section: Discussionsupporting
confidence: 89%
“…Possible causes for the precipitous decrease in leptin during fasting include changes in serum insulin and/or glucose concentrations. Insulin, because of its close relationship to appetite and body weight control (9), has been scrutinized by several groups (10)(11)(12)(13)(14)(15)(16). All but one (16) found no acute (up to 5 h) effects of hyperinsulinemia on serum leptin concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…First, both leptin and adiponectin correlated in opposite directions with body weight and BMI as expected [1,8]. Second, we confirmed that exogenous gonadotropins have a stimulatory effect, either directly or indirectly, on serum leptin levels [23] but had a minimal effect on adiponectin [3].…”
Section: Discussionsupporting
confidence: 74%
“…First, we measured fasting levels of insulin to minimize prandial fluctuations and fasting levels have been shown to correlate better with leptin [8]. Second, we measured total adiponectin instead of its various polymers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation